EFEKTIVITAS METODE MENDONGENG UNTUK MENUMBUHKAN MINAT BACA ANAK USIA DINI - Raden Siska Marini; Rosita Rosita (stit-islamic-village, 2022)
The purpose of this study was to find out how effective the storytelling method was to increase early childhood interest in reading. This research is a library research. The description of the data in this study is in the form of a record of all findings regarding the effectiveness of storytelling activities in any research discussion obtained in the literature and sources, also the latest findings regarding increasing early childhood reading interest. The results of this study indicate that the effective storytelling method for increasing interest in reading in early childhood because it is based on the results of the analysis of language development theories and theories of children's brains. Storytelling is a fun activity that can develop children's imagination curiosity. So when children have a high curiosity. Then the child will seek knowledge one of them through reading.